Tuhan dalam Basic Concept of the Quran: Pembacaan atas Pemikiran Maulana Abul Kalam Azad - Za'im Kholilatul Ummi (IAIN Bengkulu, 2020)
Studying aspects of God in religion is an important thing that must be understood. Studying the concept of God in a religion can lead people to understand religion and about values as a guide for human life. Explanation of God has experienced a long journey, is Maulana Abul Kalam Azad, a modern Islamic thinker from India, one of those who tried to explore the meaning of God. Coming from a very conservative family, Azad then tried to break away from that thinking towards modern thinking. This influenced Azad in his thinking and produced a new view of God in his interpretation, Tarjuman al-Qur'an. In this paper we will discuss the meaning of God in Surah al-Fatihah which according to Azad in it is the main content of the Koran, in the book Basic Concept of the Quran, a summary book Tarjuman al-Qur'an Azad about the interpretation of Surah al-Fatihah. The meaning of God carried out by Azad was found in his interpretation of Surah al-Fatihah with the conclusion that God has three distinct but interrelated attributes namely rububiyyah, rahmah, and ‘are. Azad's reading of the Qur'an was carried out using a textual-theological approach and a comparative approach to religion.